Tailoring Magnetic Features in Zigzag-Edged Nanographenes by Controlled Diels–Alder Reactions - Ajayakumar, M. R.; Fu, Yubin; Liu, Fupin; Komber, Hartmut; Tkachova, Valeriya; Xu, Chi; Zhou, Shengqiang; Popov, Alexey A.; Liu, Junzhi; Feng, Xinliang (Chemistry - A European Journal, 2020)
Nanographenes (NGs) with tunable electronic and magnetic properties have attracted enormous attention in the realm of carbon-based nanoelectronics. In particular, NGs with biradical character at the ground state are promising building units for molecular spintronics. However, most of the biradicaloids are susceptible to oxidation under ambient conditions and photolytic degradation, which hamper their further applications. Herein, we demonstrated the feasibility of tuning the magnetic properties of zigzag-edged NGs in order to enhance their stability via the controlled Diels–Alder reactions of peri-tetracene (4-PA). The unstable 4-PA (y0=0.72; half-life, t1/2=3 h) was transformed into the unprecedented benzo-peri-tetracenes (BPTs) by a one-side Diels–Alder reaction, which featured a biradical character at the ground state (y0=0.60) and exhibited remarkable stability under ambient conditions for several months. In addition, the fully zigzag-edged circumanthracenes (CAs) were achieved by two-fold or stepwise Diels–Alder reactions of 4-PA, in which the magnetic properties could be controlled by employing the corresponding dienophiles. Our work reported herein opens avenues for the synthesis of novel zigzag-edged NGs with tailor-made magnetic properties.
CRIS-Team Scopus Importer:2023-03-20
Keywords: circumacenes; Diels–Alder reaction; peri-acenes; singlet biradicals; zigzag edges